2023
DOI: 10.1177/23779608231189966
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Compliance With Standard Precautions Among Nurses

Abstract: Introduction The spread of microorganisms is caused by direct or indirect contact, respiratory droplets, and airborne transmission. Knowledge and compliance with standard precautions are crucial in preventing infection in the hospital. Objectives To assess the level of knowledge and compliance with standard precautions among registered nurses who work in military hospitals and the factors affecting compliance with standard precautions. Methods A descriptive cross-sectional study was conducted. Four hundred and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(73 reference statements)
1
0
0
Order By: Relevance
“…Results indicating low knowledge levels are also in line with other studies in Saudi Arabia (Al-Dorzi et al, 2014;Mahfouz et al, 2013). However, studies from Sana'a, Yemen (Gawad, 2017), Jordan (Ghabayen et al, 2023), China (Luo et al, 2010), Ghana, Africa (Akagbo et al, 2017), and Tanzania (Bahegwa et al, 2022), have reported a low rate of knowledge of the SP (63.8,54,50,37.0 and 22.5%,respectively). Moreover, our study illustrated a low level of knowledge in SP among nurses recruited from primary healthcare centers compared to those working in hospitals (23.2% versus 60.0%, data from source).…”
Section: Knowledge Of the Basic Sp Conceptssupporting
confidence: 88%
“…Results indicating low knowledge levels are also in line with other studies in Saudi Arabia (Al-Dorzi et al, 2014;Mahfouz et al, 2013). However, studies from Sana'a, Yemen (Gawad, 2017), Jordan (Ghabayen et al, 2023), China (Luo et al, 2010), Ghana, Africa (Akagbo et al, 2017), and Tanzania (Bahegwa et al, 2022), have reported a low rate of knowledge of the SP (63.8,54,50,37.0 and 22.5%,respectively). Moreover, our study illustrated a low level of knowledge in SP among nurses recruited from primary healthcare centers compared to those working in hospitals (23.2% versus 60.0%, data from source).…”
Section: Knowledge Of the Basic Sp Conceptssupporting
confidence: 88%